PRINCIPLES OF MEETING AND TREATMENT OF DORSAPATHIES IN PATIENTS OF DIFFERENT AGES (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
Our study provides information about the causes of dorsopathies at different ages, types, criteria for diagnosing dorsopathies, differential diagnosis, treatment and prevention principles. Today, darsopathies appear in different forms at different ages, and people suffer from their pain syndromes. During life, dorsalgia occurs in 70-90% of the population in developed countries and is observed in 20-25% of people every year. Although an episode of low back pain is often short-lived, about 25 percent of patients later develop chronic pain that causes long-term disability.